Galilea en Jerusalem as narratologiese ruimtes in die Markusevangelie: "n Kontinuering van die Lohmeyer- Lightfoot-Marxsen ketting - Eck, E. van (Hervormde teologiese studies, 1988)
Galilee and Jerusalem as narratological toponyms in the Gospel of Mark: A continuation of the Lohmeyer-Lightfoot-Marxsen chain By means of a narratological examination of the Gospel of Mark the role of the toponyms Galilee and Jerusalem as localities of interest is pointed out. It is argued that as such they are important conveyers of the ideological perspective of the narrator. The article furthermore enters into the debate surrounding the redaktiomgeschichtliche contribution of Willi Marxsen on this topic. A narratological examination of the Gospel of Mark reveals further links in the Lohmeyer-Lightfoot-Marxsen chain of thought, although at times correctives are suggested.